Genome-Wide Investigation of the Zinc Finger-Homeodomain Family Genes Reveals Potential Roles in Apple Fruit Ripening - Zheng, Xian-bo; Wu, Yao; Wang, Hao; Song, Shang-wei; Bai, Tuan-hui; Jiao, Jian; Song, Chun-hui; Pang, Hong-guang; Wang, Miao-miao (Frontiers in Genetics, 2022)
Zinc finger-homeodomain (ZF-HD) transcription factors play an important role in the regulation of plant growth and development, as well as the regulation of stress responses. Studies on the ZF-HD family genes have been conducted in many plants, however, the characteristics of this family in apple (Malus domestica) fruit remains to be poorly understood. In this study, we identified nineteen ZF-HD family genes in apple at the whole-genome scale, which were unevenly located on ten chromosomes. These MdZF-HD genes were phylogenetically divided into two subfamilies: zinc finger-homeodomain (ZHD) and MINI ZINC FINGER (MIF), and the ZHD subfamily was further classified into five groups (ZHDI–ZHDV). Analysis of the gene structures showed that most MdZF-HD genes lack introns. Gene expression analysis indicated that nine selected MdZF-HD genes were differentially responsive to 1-MCP (1-methylcyclopropene) treatment during the postharvest storage of ‘Qinguan’ apple fruit. Moreover, the transcripts of six genes were further validated in ‘Golden Delicious’ apple fruit, and five genes (MdZHD1/2/6/10/11) were significantly repressed and one gene (MdZHD7) was slightly induced by ethylene treatment. These results indicated that these six MdZF-HD genes may involve in the regulation of ethylene induced ripening process of postharvest apple fruit. These findings provide new clues for further functional investigation of ZF-HD genes, such as their roles in the regulation of fruit ripening.